Testing the demand approach to reconstruct pre-industrial agricultural output. Issue 3 (1st September 2016) - Edvinsson, Rodney
ABSTRACT: A common method to reconstruct historical national accounts is the demand approach, which calculates agricultural consumption from the development of wages and prices of agricultural and non-agricultural products assuming constant income, own price and cross price elasticities of demand. This study uses agricultural data for Sweden 1802–1950, which is more reliable than for other countries, to put the approach to test. Time series analysis shows that the demand approach could be modelled as a cointegrating relationship between per capita demand and the deflated wage. Income elasticity is estimated to +0.4. Using the estimated parameters to extrapolate Swedish agricultural consumption back to the Middle Ages accords quite well with other indicators. However, out-of-sampling shows that the 90% confidence interval is as large as ±0.15–0.25 natural logarithms.